DAMPAK STRATEGI KAMPANYE SOSIAL MINAT BACA DI KOTA MAKASSAR - Syahraeni Syahraeni; M. Iqbal Sultan; Tuti Bahfiarti (Fakultas Dakwah dan Komunikasi, 2021)
This research presents the impact of the social campaign strategy for reading interest in the city of Makassar. This research uses descriptive quantitative research methods with frequency distribution data analysis, the concept used is the campaign strategy and indicators of students' reading interest. The results showed that based on quantitative data, 71% agreed if they cared about information obtained about reading interest or anything related to reading, and also 59% of them strongly agreed that they got new knowledge and information after reading.